Low Intensity Breeding of Native Forest Trees in Argentina : Genetic Basis for their Domestication and Conservation - Pastorino, Mario Juan (Springer Nature, 2022)
The first genetic studies on forest trees in Argentina were carried out with exotic fast-growing species and in relation to their productive use. These antecedents, conducted mainly by the National Institute of Agricultural Technology (Instituto Nacional de Tecnología Agropecuaria, INTA), date back to the 1950s and were based on field trials of poplars, willows, pines, and eucalypts, which were eventually developed as formal genetic improvement programs (Marcó et al. 2016). It was not until the 1980s that genetic studies of native forest species began. The initial work was carried out at the University of Buenos Aires, where the first doctoral thesis on population genetics of a native forest species (Saidman 1985) was defended. Since the 1990s, new scientific groups commenced to develop with similar lines of research, in several INTA groups and in other national universities such as Comahue, Misiones, and Córdoba, expanding the objects of study to a variety of genera and species. In the beginning, the lack of knowledge about the genetic resources of the forest species from Argentina promoted studies of genetic characterization of their natural populations, by means of genetic markers (initially isoenzymes and then RAPD, AFLP, RFLP, and more recently SSR). These first steps advanced toward the study of demo-stochastic evolutionary processes (i.e., drift and gene flow) using neutral genetic markers as tools, and a little later, toward the study of adaptation and phenotypic plasticity through the analysis of variation in quantitative traits in common garden trials. Currently, this type of approach continues to expand the range of species involved and questions addressed, and furthermore, the use of new tools for thegeneration of genomic resources, the identification of candidate genes, and the analysis of full transcriptomes have been added to study selection processes also with molecular markers. Based on the knowledge gained about the genetic resources of native forest trees but focusing on their use, INTA (with the collaboration of research groups from other institutions) formally initiated domestication programs for the most relevant species in 2006, which finally led to the development of low-intensity breeding programs. Given its national projection, INTA implements these programs throughout the country, covering all forest ecosystems in Argentina. For the selection of species, in addition to practical aspects such as the region of concern of each research group, the ecological and/or productive value (current or potential) of the species considered was weighted.